Spotted! Remote camera traps used in a novel design reveal a perilous situation for the Critically Endangered Northwest African cheetah (Acinonyx jubatus hecki) in a conflict‐affected protected area in Benin - Marine Drouilly; Audrey Ipavec; Oksana Grente; Robin Horion; Aurlus Ouindeyama; Philipp Henschel; Vincent Lapeyre; Yekini Chabi N'Diaye; Ali Shams; Christine Breitenmoser; Sarah M. Durant (Ecological Solutions and Evidence)
Abstract Large mammals play critical roles in ecosystems, yet 60% are threatened with extinction and populations continue to decrease. Declines are particularly precipitous in conflict‐affected areas, disrupting ecosystems and reducing chances of post‐conflict recovery. Large carnivores are disproportionately impacted by armed conflict, yet information on population status is lacking in areas affected by insecurity because the intense survey effort required poses risks to human safety. The globally important W‐Arly‐Pendjari (WAP) ecosystem is increasingly affected by conflict and supports one of the four known remaining populations of the Critically Endangered, yet poorly documented, Northwest African cheetah (Acinonyx jubatus hecki). We used camera traps in a novel dual placement design over three biennial surveys to generate reliable and repeatable estimates for cheetah in Pendjari National Park and its surrounding hunting zones. Our design ensured detection of sufficient individuals and recaptures to allow density estimation and could be adapted for other rare, low‐density species. The two best multi‐session hybrid mixture spatially‐explicit capture recapture (SECR) models estimated a density of 0.26 ± 0.10 SE individual/100 km2 across the 4839 km2 survey area, or 0.51 ± 0.16 SE individual/100 km2 in Pendjari National Park and zero density in the adjacent hunting zones. The sex ratio was female‐biased, and females moved over more than twice the area of males, in agreement with studies elsewhere. Cheetahs showed strong crepuscular activity patterns, but males were also active before sunrise and after sunset. Practical implication: Our results indicate that Pendjari National Park is likely to be a core area for cheetah in this ecosystem and may be an important source population for the WAP Complex; however, the cheetah population is worryingly small. Violent extremism and insecurity are widespread across the remaining distribution of A. j. hecki and hence, we recommend that our approach, which minimises on‐the‐ground fieldwork, be used to provide vital data to prioritise and assess conservation interventions. We also recommend targeted protection and financial support to bolster the remaining key core population of A. j. hecki and their prey. Our results highlight the urgent need for effective and coordinated action to prevent the loss of this iconic cheetah subspecies.